Morphometric and Molecular Identification of Eimeria Bovis and Eimeria Zuernii on Beef Cattle in Lamongan, East Java, Indonesia - Kurniawan, Muhammad 'Ahdi; Suwanti, Lucia Tri; Mufasirin, Mufasirin; Suprihati, Endang; Hastutiek, Poedji; Kusnoto, Kusnoto; Ansori, Arif Nur Muhammad; Puspitasari, Yulianna; Khairullah, Aswin Rafif; Moses, Ikechukwu Benjamin; Pratama, Bima Putra; Riwu, Katty Hendriana Priscilia (Universitas Airlangga, 2025)
Lamongan Regency, located in East Java, Indonesia, is a significant center for beef cattle production. Despite its prominence, studies on the identification and differentiation of Eimeria spp. parasites in this region are notably lacking. This research aims to address this gap by evaluating the prevalence of Eimeria spp. and identifying two pathogenic species: Eimeria bovis and Eimeria zuernii. The study involved the collection of 250 fecal samples from beef cattle raised on smallholder farms across Lamongan. Sampling was conducted during the rainy season to optimize the detection of Eimeria infections. Using the sugar flotation method, Eimeria oocysts were isolated from 5–10 g of fecal matter per sample. Molecular identification employed polymerase chain reaction (PCR) assays targeting ribosomal RNA’s internal transcribed spacer 1 (ITS-1) region to detect the pathogenic species. Fecal examination using the Whitlock test revealed a prevalence of Eimeria spp. at 44.45% (111/250). PCR analysis further identified E. bovis with a 238 bp amplicon in Solokuro District and E. zuernii with a 344 bp amplicon in Tikung District, highlighting the presence of these two pathogenic species in distinct geographic areas. The findings underline the need for further research that includes expanded sampling from different regions and cattle breeds and the application of varied diagnostic methods. Such studies will contribute to a more comprehensive understanding of the genetic diversity, distribution, and epidemiology of E. bovis and E. zuernii in Indonesia, supporting improved cattle health and management practices in the region.